REALIZATION OF AN ONLINE LEARNING COURSE IN EDUCATION OF INFORMATICS SUBJECTS - MRAZEK, Michal (Trends in education, 2017)
One of the goals of the Digital Education Strategy until year 2020 is to develop information thinking for teachers. This article focuses on the possibilities of realization of online educational courses in computer science teaching in the training of future teachers. The proposed theoretical concept of the online course using Bloom's revised taxonomy could be one of the possibilities of developing information thinking, especially in programming and algorithms. Within the framework of the theoretical concept of the course a project is being prepared that aims to find out whether there is a more appropriate course structure that would further support the development of information thinking.
Keywords: Computational thinking; online courses; blended learning; The Bloom's taxonomy by Fuller